Workplace Safety and Screening of Healthcare Workers for SARS-CoV-2 at a Tertiary Care Hospital in the Northern Emirates of United Arab Emirates - Pooja Shivappa; Satyam Parmar; Godfred A. Menezes; Priyadharshini Sekar; Hafiz Ahmad; Ashfaque Hossain (Journal of Pharmacy and Bioallied Sciences)
Background: Coronavirus disease 2019 (COVID-19) was first reported in December 2019 in Wuhan, People’s Republic of China, and caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), As the virus took hold in the world, health experts paced efforts to solve the unknown nature of this threat. Methodology: We studied the clinical characteristics, laboratory biomarkers of healthcare workers in the single center, analytical cross-sectional study conducted in tertiary care hospital of the UAE. Sample size of 600 HCWs were screened for SARS-CoV-2 by real-time reverse transcription polymerase chain reaction (rRT-PCR) assay using Seegene Allplex and Andis FAST SARS-CoV-2 RT-qPCR detection kits for a period of 6 months. Findings: All the health care workers (HCWs) were vaccinated for the SARS-CoV-2. Out of these, 240 HCWs were reported to be positive. rRT-PCR with a Ct value of <38 was taken as positive >38. The laboratory investigations of the positive cases were collected and analysed further. A comparison of the laboratory tests was made between (I) COVID severe (Ct < 25) and nonsevere (Ct > 25) groups and (II) frontline workers and non-frontline workers. Besides finding short-term and sudden relief, investigators directed their efforts to provide a long-term solution for an ensuing pandemic that influenced all areas of life in unprecedented ways. Conclusion: Awareness among healthcare workers and further long-term studies focusing on their mental health the overall wellness and especially the psychological burden on doctors have received heightened awareness in media and research publications. This information can assist in developing surveillance and infection and control policies and preparedness for future COVID epidemics in similar scenarios in the future.